2022
DOI: 10.1038/s41598-022-20431-0
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of sustained physical activity from middle age to early old age on quality of life in early old age

Abstract: This study aimed to examine changes in physical activity (PA) over time (2009–2017) in the same participants and to determine an association between changes in PA and health-related quality of life (HRQoL) in early older adults (n = 994) using data from the Korea Health Panel Survey. HRQoL was measured using the EuroQol system, and the amount of PA was grouped into four activity levels: remained inactive, became inactive, became active, and remained active. The association of changes in PA over 8 years with HR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…At the same time, studies have shown that long-term regular exercise is also conducive to relieving patients’ emotions and improving their quality of life. At the same time, studies have shown that muscle strength is related to the quality of life of the older adults individuals ( 69 ), and long-term regular exercise can also help the older adults individuals improve their quality of life ( 69 , 70 ). People with diabetes are advised to exercise regularly to control blood sugar fluctuations.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, studies have shown that long-term regular exercise is also conducive to relieving patients’ emotions and improving their quality of life. At the same time, studies have shown that muscle strength is related to the quality of life of the older adults individuals ( 69 ), and long-term regular exercise can also help the older adults individuals improve their quality of life ( 69 , 70 ). People with diabetes are advised to exercise regularly to control blood sugar fluctuations.…”
Section: Discussionmentioning
confidence: 99%
“…Given the links between regular PA and RT for physical and psychological QoL and health benefits, it would be advantageous to recommend PA and RT as a proactive strategy more so than a reactive measure to declining FC or QoL. Early intervention, even during early-middle-age, may mitigate the decline in FC, QoL and cognitive health, with any improvement likely carried over to later life [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%